Dissolution state of cellulose in aqueous systems. 2. Acidic solvents. (20th October 2016) - Alves, Luis; Medronho, Bruno; Antunes, Filipe E.; Topgaard, Daniel; Lindman, Björn
Highlights: PT ssNMR allows the study of dissolved and solid fractions in a single step. Acidic solvents lead to degradation of cellulose in solution. Is possible identify cellulose degradation products in solution by PT ssNMR. C6 carbon is preferentially protonated/deprotonated when extreme pHs are used. Abstract: Cellulose is insoluble in water but can be dissolved in strong acidic or alkaline conditions. How well dissolved cellulose is in solution and how it organizes are key questions often neglected in literature. The typical low pH required for dissolving cellulose in acidic solvents limits the use of typical characterization techniques. In this respect, Polarization Transfer Solid State NMR (PT ssNMR) emerges as a reliable alternative. In this work, combining PT ssNMR, microscopic techniques and X-ray diffraction, a set of different acidic systems (phosphoric acid/water, sulfuric acid/glycerol and zinc chloride/water) is investigated. The studied solvent systems are capable to efficiently dissolve cellulose, although degradation occurs to some extent. PT ssNMR is capable to identify the liquid and solid fractions of cellulose, the degradation products and it is also sensitive to gelation. The materials regenerated from the acidic dopes were found to be highly sensitive to the solvent system and to the presence of amphiphilic additives in solution.